(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Goods and Services Tax is an indirect tax used in India on the supply of goods and services. It is a comprehensive, multistage, destination-based tax: comprehensive because subsumed almost all the indirect taxes except a few state taxes. Restaurants and Food service businesses in India, is the fastest growing business. Therefore, due to the changes in tax collection framework the development of the business is being affected. India is known as a food loving country where each and every state has its own unique cuisine. The key contributors of the growth of restaurants and food and service businesses in India are the middleclass sector. As the few sections of the society are upgrading such as lifestyle, rising agenda of women empowerment, high consumable income and reliable portable system accessibility, these upgrading sections are contributing in the development of most of the businesses in the country. The entry of multinational fast-food chain in India has changed the restaurant market. Immense rise of the Quick Service Restaurant (QSR) industry in India gave a clear way to the multinational fast-food chains and in the past few years we have seen the establishment of number of multinational fast-food chains in different regions of the country, for example, Dominos, Pizza Hut, KFC, and so forth. As the concept of quick service restaurant was booming on the other hand the eating style of consumer was also changing. Data has been collected from 120 respondents from the study area. Convenience sampling method is used while selecting the samples. The purpose of this paper is to study the customer perception towards GST with reference to restaurants.